Cover Picture: Modeling of S‐Nitrosothiol–Thiol Reactions of Biological Significance: HNO Production by S‐Thiolation Requires a Proton Shuttle and Stabilization of Polar Intermediates (ChemBioChem 8/2017). (29th March 2017) - Ivanova, Lena V.; Cibich, Daniel; Deye, Gregory; Talipov, Marat R.; Timerghazin, Qadir K.
Abstract : The cover picture shows the main mechanistic steps toward the formation of nitroxyl, HNO—a potent bioactive molecule with a range of effects on the cardiovascular system—from S ‐nitrosothiols (RSNOs), which are ubiquitous biological derivatives of nitric oxide. RSNOs have long been suspected to be potential sources of endogenous HNO through S‐thiolation reaction with thiols, although the overwhelming majority of reported RSNO–thiol reactions in vitro occur through an alternative trans‐S‐nitrosation pathway that does not yield HNO. In this issue, we show that the unusual antagonistic nature of RSNOs (shown as yin–yang in the picture) makes the S‐thiolation reaction ripe for enzymatic catalysis, as the main steps of the reaction—proton transfer and formation of an unusual zwitterionic intermediate—can be effectively facilitated by the protein environment. We thank Caroline Kenwood and Carrie Hölzer (Milwaukee High School of the Arts) for their help with the graphic; the painting is by Caroline Kenwood. More information can be found in the full paper by Q. K. Timerghazin et al. onpage 726 in Issue 8, 2017 (DOI:10.1002/cbic.201600556 ).